Multidetector-row Computed Tomography Analysis of the Radial Midpalmar Flap: A Retrospective Anatomical Study - Tien Linh Nguyen Doan, MD, PhD; Shimpei Ono, MD, PhD; Goh Akiyama, MD, PhD; Hoyu Cho, MD; Hiromitsu Hayashi, MD, PhD; Rei Ogawa, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. Soft tissue defects on the palm side of the thumb can be effectively covered by using the radial midpalmar (RMP) flap, which is usually harvested as a pedicled flap. However, previous anatomical studies on this flap are limited. We analyzed multidetector-row computed tomography angiograms of the radial midpalm of hands to more precisely characterize the 3-dimensional anatomical structure of the perforators in living patients. Methods:. This retrospective cross-sectional study included all eligible patients from 2014 to 2019. All Digital Imaging and Communications in Medicine (DICOM) data were analyzed by the DICOM viewer. RMP area vascularization pattern and cutaneous perforator number, location, origin, internal diameters, and bifurcation-to-dermis lengths were recorded. Results:. In total, 41 perforators were found in 30 patients: 21 patients had 1 perforator, 7 had 2, and 2 had 3 perforators. All were located inside a 23.2-mm diameter circle with an origin on the second metacarpal bone axis approximately 10 mm distally from the Kaplan cardinal line. Their origins were the superficial palmar arch system (61%), palmar arteries of the thumb (24%), and radialis indicis artery (15%). The mean perforator diameter and length were 0.61 and 8.48 mm, respectively. Conclusions:. All patients had at least 1 reliable perforator in the radial midpalm. Our results suggest that plastic surgeons can easily and safely plan the RMP flap design, potentially without preoperative perforator mapping. Guidelines for this flap are proposed.